The Comparison of Body Image, Quality of Sleep and Marital Satisfaction among Substance Abuser and Non-substance Abuser Women - Sara Behzad; Anahita Khodabakhshi Koolaee; Davoud Taghvaee (Shahid Beheshti University of Medical Sciences, 2016)
Background and Objective: The previous research has demonstrated that addiction treatment services for women need to be based on knowledge of female psychological needs. Therefore, the aim of current study is to compare body image, quality of sleep and marital satisfaction among substance abuser and non-substance abuser women. Materials and Methods: This study is a descriptive comparative research. 200 women including 100 substance abuser women and 100 non-substance abuser women were chosen through convenience method in Arak in 2015. The measuring instruments were Fisher body image scale (1970), Pittsburgh Sleep Quality Index (1989) and Enrich Marital Satisfaction Scale (1989). Data was analyzed utilizing t independent. Results: The results showed that there is the significant difference between marital satisfaction (P=0.001) and quality of sleep (P=0.001) among substance abuser and non-substance abuser women. Additionally, the significant difference was not observed between body image (P= 0.31) among these two groups. Conclusion: These findings emphasized that substance use decreases the quality of sleep and marital satisfaction in women. Hence, it should be considered these factors in process of therapeutic intervention in substance abuser women.